Apigenin attenuates atherosclerosis and non-alcoholic fatty liver disease through inhibition of NLRP3 inflammasome in mice - Zheng Lu; Lu Liu; Shunxin Zhao; Jiangtao Zhao; Sujun Li; Mingyang Li (Scientific Reports, 2023)
Abstract Apigenin (APN), a flavone found in several plant foods with various biological properties such as anti-obesity, anti-inflammation and other abilities, alleviates atherosclerosis and non-alcoholic fatty liver disease (NAFLD) induced by a high fat diet (HFD) in mice. However, the underlying mechanisms have not been fully understood. In this study, we investigated the role of NLRP3 in anti-atherosclerosis and anti-NAFLD effect of APN in mouse models with NLRP3 deficiency. Atherosclerosis and NAFLD models were established by treatment of low density lipoprotein receptor-deficient (Ldlr −/− ) mice and NLRP3 −/− Ldlr −/− mice with a HFD diet (20% fat and 0.5% cholesterol) with or without APN. En face lipid accumulation analysis, plasma lipid levels, hepatic lipid accumulation and inflammation were analyzed and quantified. For in vitro experiments, HepG2 cells were stimulated by LPS plus oleic acid (OA) in the absence or presence of APN (50 μM). Lipid accumulation and the effect of APN on the NLRP3/NF-κB signaling pathway were investigated. APN administration partly reversed atherosclerosis and hepatic lipid accumulation, and decreased body weight and plasma lipid levels in Ldlr −/− mice when fed a HFD. Compared with Ldlr −/− mice, NLRP3 −/− Ldlr −/− mice showed more severe atherosclerosis and hepatic lipid accumulation. Treating the HepG2 cells with APN reduced lipid accumulation. APN also inhibited activation of the NLRP3/ NF-κB signaling pathway stimulated by OA together with LPS. Our results indicate that APN supplementation prevents atherosclerosis and NAFLD via NLRP3 inhibition in mice, and suggest that APN might be a potential therapeutic agent for the prevention of atherosclerosis and NAFLD.